2021
DOI: 10.2147/ijwh.s264023
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Lifestyle Focused Approaches into the Management of Primary Dysmenorrhea: Impact on Quality of Life

Abstract: Objective: This narrative review aims to identify alternative ways to improve the symptoms of primary dysmenorrhea (PD). Background: PD refers to endometrial painful cramps during the premenstrual period. This condition affects a lot of women worldwide and is accompanied with absenteeism and high economic costs, thus, risk-free, and effective therapeutic approaches are needed. Pharmacological agents such as non-steroidal anti-inflammatory drugs (NSAIDs) and oral contraceptive pills (OCPs), which are widely pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
0
10
0
1
Order By: Relevance
“…A meta-analysis study indicated that exercise and physical activity reduced the intensity of pain and other symptoms related to menstruation (20). Ortiz stated that probably 50 minutes of exercise three times a week could have positive effects in reducing menstrual pain (1,11). Another study reported that home exercise could lead to a significant improvement in the QOL related to health and pain in patients with dysmenorrhea (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis study indicated that exercise and physical activity reduced the intensity of pain and other symptoms related to menstruation (20). Ortiz stated that probably 50 minutes of exercise three times a week could have positive effects in reducing menstrual pain (1,11). Another study reported that home exercise could lead to a significant improvement in the QOL related to health and pain in patients with dysmenorrhea (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as recurrent menstrual cramps of uterine origin without obvious medical pathology, causing physical, mental, and social changes such as mood swings and socioeconomic changes. It can also cause considerable restrictions on all activities (1,2). Dysmenorrhea affects between 45 -95% of women with menstrual periods (3).…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde primer dismenoreyi önlemede yoga, ağrı süresini ve şiddetini azaltmada mükemmel bir araç olarak kabul edilmiştir. İzometrik egzersiz ve germe, koşma, Kegel egzersizleri ve gevşeme duruşları gibi diğer fiziksel aktivite biçimlerinin de düzenli olarak yapıldığında dismenorede ağrı ve rahatsızlığı gidermek için önerildiği belirlenmiştir (Tsonis et. al.…”
Section: Discussionunclassified
“…Various lifestyle interventions and alternative medicine have reported to be effective in treating dysmenorrhea [33,34]. Women have been found to have distorted body image due to PD, and treatment by certain physiotherapeutic approaches like heat therapy, spinal manipulations and electrotherapy, as well as KT, are reported to be effective [21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%